The Herbal Compound Thymol Targets Multiple Salmonella Typhimurium Virulence Factors for Lon Protease Degradation - Zhang, Yong; Liu, Yan; Luo, Jingjing; Jie, Jing; Deng, Xuming; Song, Lei (Frontiers in Pharmacology, 2021)
Many important bacterial pathogens using type III secretion system to deliver effectors into host cells. Salmonella Typhimurium (S. typhimurium) is a pathogenic Gram-negative bacterium with type III secretion system as its major virulence factor. Our previous studies demonstrated that thymol, a monoterpene phenol derivative of cymene inhibited S. typhimurium invasion into mammalian cells and protected mice from infection. However, the anti-bacterial mechanism of thymol is not clear. In this study, we revealed that that thymol interferes with the abundance of about 100 bacterial proteins though proteomics analysis. Among the 42 proteins whose abundance was reduced, 11 were important virulence factors associated with T3SS-1. Further analyses with SipA revealed that thymol directly interacts with this protein to induce conformational changes, which make it susceptible to the Lon protease. In agreement with this observation, thymol effectively blocks cell invasion by S. Typhimurium. Thus, thymol represents a class of anti-virulence compounds that function by targeting pathogenic factors for degradation.